Peningkatan Resiliensi Kelompok Petani Padi terhadap Banjir melalui Pemilihan Varietas di Desa Ciuyah, Kabupaten Cirebon - Anggi Nindita; Sriwulan Ferindian Falatehan; Muhammad Aries; Dina Nurdinawati; Sholichin Sholichin (Institut Pertanian Bogor, 2026)
Flood disasters, as one of the major impacts of climate change, often exert significant pressure on rice-farming communities, particularly in sustaining production and ensuring food security. Strengthening the resilience of farmer groups in flood-prone areas requires targeted learning processes and well-structured social organization. These two aspects are essential in enhancing resilience through: a) The selection of rice varieties adaptive to climate change and b) The utilization of social institutions to address flood challenges. The Dosen Pulang Kampung (Dospulkam) program of IPB University was implemented in Ciuyah Village, Cirebon regency, to facilitate resilience improvement among rice farmer groups through an integrated training program. The training encompassed the selection of rice varieties and the enhancement of farmer group capacity in managing irrigation resources. The integrated training was conducted from 7‒9 July 2025. The method was conducted through focus group discussions (FGDs), small group discussions, lectures, field surveys, and the distribution of stimulus assistance in the form of IPB 9G seeds, IPB 13S seeds, and IPB 9G rice. Training participants were organized at two levels: group and village. At the community level, 23 community participants represented eight groups from the village; meanwhile, decision-makers, including the village government, the Combined Farmers Group, and village extension workers, were also involved. The results indicated that farmer groups developed a strong understanding of the use of IPB 9G as a climate-smart variety and optimized collective action through social institutions to address irrigation channel constraints. This program has contributed to enhancing the adaptive capacity of rice farmer groups to flood disasters caused by climate change.